A Protocol for a Systematic Review of CGIAR’s Research (2012-2023) on Climate-Induced Extreme Rainfall and Floods - Chikozho, C.; Managa L.R.; Kujinga, K.; Bosire, Caroline K.; Mukherji, Aditi (CGIAR System Organization, 2024)
Background - Despite the implementation of targeted research and agricultural extension interventions in various parts of the world, climate change and extreme rainfall events continue to significantly exert adverse impacts on agricultural production and food security. In this regard, the increased frequency of climate change-related extreme rainfall and floods in recent years has worsened the risks faced by farmers. A substantial amount of research on climate change, extreme rainfall and floods have already been completed within the Consultative Group on International Agricultural Research, demonstrating diverse implications across geographies, commodities, and populations. However, there is a need to provide a synthesized and comprehensive analysis of this research corpus to advance the understanding of the current state of knowledge in this area, identify knowledge gaps and inform future studies. This protocol provides a roadmap for the synthesis of CGIAR research in the space of hazards arising from climate-induced extreme rainfall and floods and associated adaptation solutions. It assesses the impacts of these solutions, as well as the impacts of extreme rainfall and floods on natural, agricultural, and human systems. The protocol includes an examination of the methods employed to estimate the impacts. Ultimately, this review will identify possible entry-points for supporting the upscaling of any impactful interventions designed in this landscape. Methods - The review will follow the Reporting Standards for Systematic Evidence Syntheses (ROSES) processes. As part of article selection, machine learning was deployed to semi-automate identification of existing relevant CGIAR literature from Nine CGIAR institution data repositories, specifically focusing on the impact of climate-induced extreme rainfall and floods on agricultural production and food security, with English being used as the main language. The search results from this database were exported into Excel, merged, and then imported into a new Rayyan project. Duplicates were removed, while titles and abstracts were double-screened using specific inclusion-exclusion criteria. The screening and selection of studies were conducted by two independent researchers. During the review and synthesis process, data will be extracted using artificial intelligence software, and a codebook will be developed to ensure consistency and reproducibility. The review and detailed narrative synthesis will focus on the methods, adaptation solutions, and impacts of CGIAR research related to climate-induced extreme rainfall and floods. Analysis of the data will also be guided by our understanding of livelihoods and food security imperatives. Results - Out of 2846 identified papers, 107 studies met our search criteria and will be included in this systematic review. Preliminary insights from the included papers show that several innovations can be deployed by farmers to address extreme rainfall and floods. This includes the deployment of climate-smart agricultural innovations, use of early-warning systems for extreme rainfall and floods, the design and implementation of national policies and institutions that support adaptation and institutionalizing anticipatory action that can be taken at the local and national level to mitigate the impacts of extreme rainfall and floods. Conclusion - This systematic review is intended to provide a comprehensive understanding of the current state of knowledge on climate-induced extreme rainfall and floods within the CGIAR, identify critical knowledge gaps, and inform future research priorities to enhance crop resilience and food security. Ultimately, the review will identify possible entry-points for supporting the upscaling of any impactful interventions designed in this landscape. Key actors in the climate change and food security sector are called upon to support interventions that address the impacts of extreme rainfall and floods on agricultural production. Strengthening policy and institutional frameworks is particularly urgent to enhance adaptation efforts for the risks and impacts of extreme rainfall and floods in small-scale farming systems.